Social cognition as an RDoC domain. Issue 1 (26th November 2015) - Gur, Ruben C.; Gur, Raquel E.
Abstract : While the bulk of research into neural substrates of behavior and psychopathology has focused on cognitive, memory and executive functions, there has been a recent surge of interest in emotion processing and social cognition, manifested in designating Social Cognition as a major RDoC domain. We describe the origins of this field's influence on cognitive neuroscience and highlight the most salient findings leading to the characterization of the "social brain" and the establishments of parameters that quantify normative and aberrant behaviors. Such parameters of behavior and neurobiology are required for a potentially successful RDoC construct, especially if heritability is established, because of the need to link with genomic systems. We proceed to illustrate how a social cognition measure can be used within the RDoC framework by presenting a task of facial emotion identification. We show that performance is sensitive to normative individual differences related to age and sex and to deficits associated with schizophrenia and other psychotic disorders. Neuroimaging studies with this task demonstrate that it recruits limbic and frontal regulatory activation in healthy samples as well as abnormalities in psychiatric populations. Evidence for its heritability was documented in genomic family studies and in patients with the 22q11.2 deletion syndrome. Measures that meet such criteria can help build translational bridges between cellular molecular mechanisms and behavior that elucidate aberrations related to psychopathology. Such links will transcend current diagnostic classifications and ultimately lead to a mechanistically based diagnostic nomenclature. Establishing such bridges will provide the elements necessary for early detection and scientifically grounded intervention. © 2015 Wiley Periodicals, Inc.